RIFM fragrance ingredient safety assessment, 2-ethyl-1-butanol, CAS Registry Number 97-95-0. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current conditions is supported by existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, as well as environmental safety. Data from the suitable read across analog 2-ethylhexanol (CAS # 104-76-7) show that this material is not genotoxic. Data from the suitable read across analog isopropyl alcohol (CAS # 67-63-0) show that this material does not have skin sensitization potential. The local respiratory toxicity endpoint was completed using the TTC (Threshold of Toxicological Concern) for a Cramer Class I material (1.4 mg/day). The repeated dose toxicity endpoint was completed using 2-ethylhexanol (CAS # 104-76-7) and 1-heptanol, 2-propyl (CAS # 10042-59-8) as suitable read across analogs, which provided a MOE > 100. The developmental and reproductive toxicity endpoint was completed using 2-ethyl-hexanol (CAS # 104-76-7) and isobutyl alcohol (CAS # 78-83-1) as suitable read across analogs, which provided a MOE > 100. The phototoxicity/photoallergenicity endpoint was completed based on suitable UV spectra. The environmental endpoint was completed as described in the RIFM Framework. Highlights: 2-Ethyl-1-butanol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using data on the target material, read across and/or TTC.